Persepsi Guru terhadap Soal Asesmen Kompetensi Minimum (AKM) Literasi Membaca di SMP - Familiyana, Lisna; Harjono, Hary Soedarto; Suryani, Irma (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
The Minimum Competency Assessment (AKM) as an assessment of the basic competencies needed by students will definitely experience changes in its application. This will certainly encourage alternatives for every educator in developing student self-capacity. For this situation, educators will certainly have their own perspective in relation to the information they have. The desired data actually wants to describe how the teachers understand in terms of AKM questions, especially understanding abilities. The focus of the deepening that will be completed is on the types of AKM questions which consist of various decisions, many complex decisions, matchmaking, short sections, and a description of the types of AKM reading ability questions that they have in their respective schools. The purpose of this study, among others, is to describe the teacher's perception of the AKM reading literacy question in junior high school. The research activity was directed at a junior high school in Tanah Sepenggal Lintas, Bungo Regency. Qualitative descriptive method with interview method will answer the purpose of this research. Information from this exploration is as a meeting directed at three educators from various subjects and skilled in their respective fields. This exploration uses a subjective methodology with a contextual investigative strategy. Information gathering strategy by utilizing meetings and documentation studies. Information investigation strategies used are decline, show, and end. As a result of this review, it can be assumed that the teacher's impression of the AKM reading skill in junior high school received a positive reaction. This has to be seen from the side effects of inside and outside interviews directed with educators.